Relocation of the Hypocenter of an Earthquake with the Double Difference Method in the Regional Study Area of Yogyakarta: Relokasi Hiposenter Gempabumi menggunakan Metode Double Difference Wilayah Kajian Daerah Istimewa Yogyakarta - Fani Rohmiasih; Andi Andi; Nugroho Budi Wibowo (JURNAL GEOCELEBES, 2023)
The relocation of the earthquake hypocentre is necessary in order to determine the position of the earthquake centre with higher accuracy. An accurate hypocentre position is important for earthquake-prone areas mapping, seismicity analysis, and fault zone identification. The double difference algorithm technique using the hypoDD program can be used for hypocentre relocation. This article reports the earthquake relocation of 23 earthquakes in the Yogyakarta region recorded at four observation stations. The result shows that the hypocentre shift spreads randomly with a shift distance of less than 20 km, with the most shifting direction of the epicentre to the northeast. The Earthquake’s hypocentre after relocation in the land area is estimated to be triggered by a fault under the Gamping Wungkal Formation, while the earthquake around Mount Merapi is estimated to be triggered by volcanic activity. The Relocation result in the sea area show that the hypocentre leads to the subduction line.